Celle des riches et celle des pauvres - Bernard Roussel; Feleke Woldeyes (Revue d'ethnoécologie)
Seeds of false cardamom kororima (Aframomum corrorima (Braun) Jansen), malagueta pepper endemic of Ethiopia, is an unavoidable spice, emblematic of the whole country with multiple uses and quite routine uses. Spontaneous within the lowest stratum of the Kafa moist forest, it is also a cultivated plant in the gardens of several regions in southern Ethiopia.This paper, starting from the analysis of production and commercial chains of kororima, aims to put light on the relation between provenances, specificity and quality on the national Ethiopian market. At the national level, various localized productions of kororima converge into two main commercial chains well separated of which final products are named after the two main zones of production : classically, kororima from Gofa and kororima from Kafa are not competing and one can find the two provenances in each shop and spice corners of Addis Ababa markets. Clearly distinguished by the actors of the commercial chain who recognize perfectly the specificities (aspect, colour, odour, taste), they are considered as two products of two different qualities resulting from conditions of production (spontaneous/cultivated), way of transformation, and drying processes.Since a few decades, there have been valorisation efforts of products coming from coffee forest ecosystems as well as homegardens of Ethiopia in order to contribute to conservation of the rich and unique forest and garden biodiversity. In this context, kororima appears as a very convenient product and numerous initiatives of commercialization have been set up.These two products are targeted/end up for two categories of consumers and utilization. Gofa kororima, which is of higher quality, is sold at higher price to well off consumer for more valorised purposes. Recent effort of promoting Kafa kororima, which quality has been ameliorated, is facing to the consumption habit and existing commercialization patterns. Various provenances which quality has been ameliorated have some difficulties to find a good place in the market.